2020
DOI: 10.4103/jfmpc.jfmpc_520_20
|View full text |Cite
|
Sign up to set email alerts
|

Surgical coverage of cataract in a rural area of north India: A cross-sectional study

Abstract: Background: India has the highest number of blind people globally, unoperated cataract being the most common cause of blindness and low vision. Although safe and effective cataract surgical techniques are available, the cataract burden continues to increase annually, due to the backlog of patients to be operated upon, and a growing number of cataract cases due to increased life expectancy. Aim: To assess cataract surgical coverage (CSC) in a rural area of north India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Sobti S. et al .,[ 22 ] reported that India has the highest number of blind people globally, unoperated cataract being the most common cause of blindness and low vision. Although safe and effective surgical techniques are available, the cataract burden continues to increase annually, due to the backlog of patients to be operated upon and a growing number of cataract cases due to increase life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…Sobti S. et al .,[ 22 ] reported that India has the highest number of blind people globally, unoperated cataract being the most common cause of blindness and low vision. Although safe and effective surgical techniques are available, the cataract burden continues to increase annually, due to the backlog of patients to be operated upon and a growing number of cataract cases due to increase life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Its effect may be predominant in developing countries like India, considering its vast aging population with increased life expectancy and the tremendous cataract surgery backlog that is growing annually. [ 5 11 12 ] As this pandemic scenario is unprecedented, there is no data from India to help predict how long and to what extent the health care surgery volume will improve. We are speculating that it may take approximately 5 months and 10 months in the optimistic and ambivalent settings, respectively, to reach the pre-pandemic level of the forecasted surgical load.…”
Section: Discussionmentioning
confidence: 99%
“…The cataract surgical coverage is less in India already,[ 11 ] and to add to that the effects of the pandemic, we assume that after lifting elective surgery suspension, it will be extremely difficult to return to the pre-pandemic surgical volumes, considering the delays in manufacturing drugs/intraocular lenses and personal protective equipment and transport disruptions. [ 13 14 ] Considering the resurgence of coronavirus cases in what is deemed the “second wave,” it may further delay the recuperation to fully functional pre-COVID-19 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The annual incidence of any VI in our cohort was lower than that in India (Andhra Pradesh Eye Disease Study). Recent studies reported that cataract surgery coverage in rural China is 62.7%, 16 higher than that in rural India (43.2%), 30 which might account for the lower incidence of vision loss and reflect successful policies to promote eye health in China.…”
Section: Clinical Sciencementioning
confidence: 99%